Evaluation of Routing Algorithm for Ad-hoc and Wireless Sensor Network Protocol - Agrawal, Sujata; Kulat, K.D; Daigavane, M. B (International Journal of Computer Sciences and Engineering, 2013)
Low control overhead and Low energy consumption are two key issues in wireless ad hoc sensor networks to improve protocol efficiency. They decide the quality of service provided by the protocol. Dynamic Source Routing (DSR) and AODV (Ad hoc on demand distance vector) are preferred routing protocols in wireless sensor networks. The routing overhead of DSR and AODV is a drawback in power-constrained environment. This is directly proportional to the path length. This paper presents enhanced and efficient routing algorithms, namely EEDSR and EEAODV with a local route low energy consumption model for DSR and AODV. This model reduces the routing overhead and consumes less energy during data transfer and thus improves the efficiency of Ad Hoc sensor network.